RIPK3 Promotes JEV Replication in Neurons via Downregulation of IFI44L - Bian, Peiyu; Ye, Chuantao; Zheng, Xuyang; Luo, Chuanyu; Yang, Jiali; Li, Mengyuan; Wang, Yuan; Yang, Jing; Zhou, Yun; Zhang, Fanglin; Lian, Jianqi; Zhang, Ying; et al. (Frontiers in Microbiology, 2020)
Japanese encephalitis virus (JEV), the leading cause of viral encephalitis in Asia, is neurovirulent and neuroinvasive. Neurons are the main target of JEV infection and propagation. Receptor interacting serine/threonine-protein kinase 3 (RIPK3) has been reported to contribute to neuroinflammation and neuronal death in many central nervous system diseases. In this study, we found that the progression of JE was alleviated in RIPK3 knockout (RIPK3-/-) mice in both peripheral and intracerebral infection. RIPK3-knockdown (RIPK3-RNAi) neuro2a cells showed higher cell viability during JEV infection. Moreover, the JEV load was significantly decreased in RIPK3-/- mouse-derived primary neurons and RIPK3-RNAi neuro2a cells compared with wild-type neurons, but this was not observed in microglia. Furthermore, RNA-sequencing of brain tissues showed that the level of the IFN-induced protein 44-like gene (IFI44L) was significantly increased in JEV-infected RIPK3-/- mouse brains, RIPK3-/- neurons and RIPK3-RNAi-neuro2a cells. Then, it was demonstrated that the propagation of JEV was inhibited in IFI44L-overexpressing neuro2a cells and enhanced in IFI44L and RIPK3 double knockdown neuro2a cells. Taken together, our results showed that the increased expression of RIPK3 following JEV infection played complicated roles. On the one hand, RIPK3 participated in neuroinflammation and neuronal death during JEV infection. On the other hand, RIPK3 inhibited the expression of IFI44L to some extent, leading to the propagation of JEV in neurons, which might be a strategy for JEV to evade the cellular innate immune response.